Student Teachers’ Perceptions of Teaching: Looking Back or Moving Forward? - Škugor, Alma; Tomaš, Suzana; Letina, Alena (Revija za elementarno izobraževanje, 2025)
The aim of the study was to compare perceptions about the teaching of the subject “Nature and Society” among preservice primary school teachers at three Croatian universities. The results indicate consistent perceptions among second- and fifth-year students, regardless of their university, with a notable inclination toward teacher-centred teaching. Fifth-year students from all three universities demonstrate a slight shift away from the traditional teaching paradigm compared with second-year students. For a genuine transformation in teaching approaches, in addition to acquired knowledge and developed competences, it is essential to encourage preservice teachers to engage in self-reflection on their teaching practices to become aware of their own beliefs about teaching.
Keywords: DASTT-C, student-centred teaching, teacher-centred teaching, perception, preservice primary school teachers.